Obfuscation and Rational Inattention - JANSSEN, Aljoscha (Institutional Knowledge at Singapore Management University, 2023)
We study the behavior of duopolistic firms that can obfuscate their prices before competing on price. Obfuscation affects the rational inattentive consumers' optimal information strategy, which determines the probabilistic demand. Our model advances related models by allowing consumers to update their unrestricted prior beliefs with an informative signal of any form. We show that the game may result in an obfuscation equilibrium with high prices or a transparency equilibrium with low prices and no obfuscation, providing an argument for market regulation. Obfuscation equilibria cease to exist for low information costs and if one firm seems a priori considerably more attractive.